SOCIAL MEDIA THEORIES IN CRITICAL DISCOURSE ANALYSIS (CDA) - Zonianus Mendrofa (Universitas Muhammadiyah Makassar, 2018)
Social Media can be conceptualized as an emerging frontier where new forms of social relations expand at the junction of human collective communicative and technology of information. Discussion about CDA place in critical information systems (IS) research, With an example of a CDA study, applied to social media this discussion service to inform IS researchers of a decent option for theory building in social media.